Pengenaan Pajak Terhadap Objek Penelitian Sains yang di Impor Perspektif Maslahah Mursalah - Akbar Gunawan Siagian; Cahaya Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The imposition of import taxes is certainly very high for individuals even though the enforcement limit is at the limit of USD1,500. Even so, the imposition of this tax is also inseparable from scientific research goods such as chemical reaction goods. Chemical reaction goods are goods that produce new chemical compounds such as uranium, cobalt and mercury or laboratory practice goods. Observatory practice items are items that are used as scientific research aids such as star telescopes, electron microscopes, or medical equipment. In terms of benefits, this economic activity is also seen as not meeting the criteria for benefits. This research focuses on the discussion of the Legal Rules for the Imposition of Import Goods Tax According to the Minister of Finance Regulation No. PMK 199/PMK.10/2019 and the imposition of taxes on imported scientific research objects from the perspective of maslahah mursalah. This study uses a normative method with a normative juridical research type. The results of the study prove that the imposition of taxes on imported scientific research objects cannot be said to meet individual benefits because there are parties who consider that the tax is too high to be very detrimental personally. Although the import goods tax is beneficial for the benefit of the wider public, namely for state revenue and infrastructure maintenance.